PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA PESERTA DIDIK MENGGUNAKAN MODEL STUDENT TEAMS ACVHIEVEMENT DIVISIONS DI KELAS III SD NEGERI 45 PAYAKUMBUH - Nesa Gusveriza Putri; Desyandri; Yesi Anita; Sofyanti Engreini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learningoutcomes in Pancasila Education among third-gradestudents at SD Negeri 45 Payakumbuh. The identifiedproblems included teacher-centered learning, limiteduse of instructional media, inadequate implementationof collaborative learning activities, and students' lowparticipation, self-confidence, and responsibility duringthe learning process. This study aimed to describe theimprovement of students' learning outcomes inPancasila Education through the implementation of theStudent Teams Achievement Divisions (STAD)cooperative learning model assisted by animatedvideos. This study employed Classroom ActionResearch (CAR) using qualitative and quantitativeapproaches conducted in two cycles, consisting ofplanning, implementation, observation, and reflectionstages. The research subjects were one teacher and25 third-grade students of SD Negeri 45 Payakumbuhduring the January–June semester of the 2025/2026academic year. Data were collected throughobservation, tests, and documentation and wereanalyzed using qualitative and quantitative techniques.The findings revealed that the implementation of theSTAD cooperative learning model assisted byanimated videos improved the quality of lessonplanning from 89.55% to 95.83%, the implementationof learning activities by teachers and students from85.69% to 96.42%, and students' learning outcomes inthe affective aspect from 73.62 to 85.25, the cognitiveaspect from 75.40 to 87.76, and the psychomotoraspect from 73.75 to 85.50. Therefore, theimplementation of the STAD cooperative learningmodel assisted by animated videos effectivelyimproved the Pancasila Education learning outcomesof third-grade students at SD Negeri 45 Payakumbuh.